Are Total, Intensity- and Domain-Specific Physical Activity Levels Associated with Life Satisfaction among University Students? - Pedišić, Željko (PLoS One, 2015)
BACKGROUND: Thorough information about the relationship between physical activity (PA) and life satisfaction is still lacking. Therefore, this study examined the cross-sectional relationships between life satisfaction and meeting the World Health Organization (WHO) moderate to vigorous-intensity PA recommendations, total volume and duration of PA, intensity-specific PA (walking, moderate- and vigorous-intensity), domain-specific PA (work, transport-related, domestic, and leisure-time), and 11 domain and intensity-specific PA types among university students. Additionally, we examined the associations between life satisfaction and gender, age, disposable income, community size, smoking, alcohol intake, body mass index (BMI), and self-rated health. METHODS: The study included a random sample of 1750 university students in Zagreb, Croatia (response rate = 71.7%; 62.4% females; mean age 21.5 ± 1.8 years), using the International Physical Activity Questionnaire — long form and the Satisfaction with Life Scale. RESULTS: Higher life satisfaction was associated with female gender (β = 0.13; p = <0.001), younger age (β = -0.07; p = 0.024), higher disposable income (β = 0.10; p = 0.001), and better self-rated health (β = 0.30; p = <0.001). No significant association was found between life satisfaction and size of community (p = 0.567), smoking status (p = 0.056), alcohol consumption (p = 0.058), or BMI (p = 0.508). Among all PA variables, only leisure-time vigorous-intensity PA was significantly associated with life satisfaction after adjustments for socio-demographic characteristics, lifestyle and self-rated general health (β = 0.06; p = 0.045). CONCLUSIONS: This study indicated a weak positive relationship between leisure-time vigorous-intensity PA and life satisfaction, whilst no such association was found for other PA variables. These findings underscore the importance of analyzing domain and intensity-specific PA levels in future studies among university students, as drawing conclusions about the relationship between PA and life satisfaction based on total PA levels only may be misleading.